Declawing the dinosaurs in the science classroom: Reducing Christian teachers' anxiety and increasing their efficacy for teaching evolution. Issue 4 (8th November 2018) - Hawley, Patricia H.; Sinatra, Gale M.
Abstract: America's rank among the lowest of developed countries in evolution acceptance rates is due, at least in part, to religious and political opposition. The negative correlations among religiosity, political ideology, and evolution acceptance in the United States have been documented repeatedly, and comfort with evolution varies by region with reception being especially cool in the south and southwest. Teachers are on the frontlines of the tensions between science and faith and often avoid the topic even if such avoidance violates state laws. Even non‐creationist teachers in regions with creationist norms are pressured to conform to regional curricula preferences. The present study describes the outcomes of a professional development workshop that explicitly considerers motivational and identity features of largely conservative, religious science teachers residing in West Texas. Our goal was to reduce the perceived conflict between faith and science such that Christian teachers would feel less negative and more positive about the theory and teaching it, and thus more efficacious in the classroom such that they would be more willing to teach according to the standards. In a retrospective pretest‐posttest design, teachers reported reductions in misconceptions and negative emotions in response to the workshop, and gains in positive emotions and self‐efficacy. Change scores were particularly marked for female teachers. Moreover, the relationships between community support for teaching evolution and teacher emotions and self‐efficacy were reduced post‐workshop indicating that teachers became independent from the norms of their schools. Though not the first intervention to support teacher instruction of evolution, the present workshop is the first to our knowledge that seeks to integrate biological content, cognitive change, and motivational/identity models.